Iraq : Third and Fourth Reviews Under the Stand-By Arrangement, Financing Assurances Review, and Requests for Extension of the Arrangement and for Waiver of Nonobservance of a Performance Criterion. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses key findings of the Third and Fourth Reviews Under the Stand-By Arrangement (SBA) for Iraq. Economic growth in 2006 was below target because oil production did not increase as projected. This reflected lower-than-planned investment and the lack of security. Inflation increased to 65 percent in 2006 to December 2006. This was mainly owing to shortages of key commodities, caused in part by the ongoing insurgency. The underlying rate of inflation has also remained high.